Bipolar spectrum disorder: What evidence for pharmacological treatment? A systematic review. (December 2019) - Hede, Vincent; Favre, Sophie; Aubry, Jean-Michel; Richard-Lepouriel, Hélène
Highlights: Concept of bipolar spectrum disorder (BSD) remains unclear and heterogeneous. There is no evidence supporting efficacy of pharmacological treatment, especially mood stabilizers, for BSD. Studies are need to better define BSD and to establish guidelines for treatment. Abstract: Background and Objectives: Bipolar spectrum disorder (BSD) is an extended concept of bipolar disorder (BD) that includes conditions that do not fulfill the criteria. There is no recommendation today about its treatment. We reviewed relevant literature focusing on pharmacological treatments, looking for high-strength evidence leading to guidelines. Methodology: A literature search was conducted using MedLine / PubMed database and Google Scholar up to September 2018. Search words were related to BSD and pharmacological treatment. Results: The literature search yielded 621 articles. Out of these, 35 articles met our selection criteria. There was limited high quality data. Only one randomized control trial (RCT) and one randomized open label trial were found. Most studies used different definition of BSD. Conclusions: There is a considerable lack of data and no evidence supporting efficacy of pharmacological treatment for BSD. There is a need for a consensus on the definition of BSD and more evidence studies to evaluate drug's effectiveness in this condition.